Stakeholder Collaboration in the Development of Essential Ecosystem Area - M. Husni Tamrin; Lunariana Lubis (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Abstract. This study aims to analyze the process of collaborative governance in the development of the Ujungpangkah Mangrove (MUP) Essential Ecosystem Area (KEE) in Gresik Regency, East Java which has been established by the Governor of East Java in 2020. Collaboration between government and non-government is seen from the aspect of their respective roles each stakeholder, common understanding and goals, clarity of roles and responsibilities of each party, commitment of stakeholders in carrying out roles and responsibilities, reciprocal relationships and dependencies as well as potential conflicts and efforts made to resolve these conflicts for the sustainability of KEE-MUP as an ecotourism destination. This research uses a qualitative method with a case study approach. The results show that the dynamics of collaborative governance are not good, this can be seen from the unclear understanding and common goals among stakeholders. The collaboration scheme carried out by the government to build trust and commitment in the development of KEE must be carried out so that the roles of each stakeholder are clearly known. With these facts, common perceptions between stakeholders are needed as well as arrangements for rights and obligations in effective management, each stakeholder must bear the costs of managing KEE which is his responsibility, and is entitled to benefit from managing KEE through activities that are legally justified. As well as a partnership mechanism between stakeholders in the management of KEE, the mechanism for sharing costs and benefits must be regulated in a transparent, fair and fulfilling the principle of equality.